Systematical Study on the Influencing Factors of Synchronous Thermal Analyses of Samples-Taking the Chalcanthite as an Example - Xianzhe, Duan; Nan, Li; Yuyuan, Wang; Zhenping, Tang (Frontiers in Chemistry, 2022)
Thermal analysis is widely used for the measurement of the relationship between the temperature and physical properties of the materials. Many studies have reported different thermal analysis methods, including Thermogravimetry (TG), Derivative Thermogravimetry (DTG), Differential Heat Analysis (DTA) and Differential Scanning Caloretry (DSC), but few comprehensively studied the factors influencing TG-DTA by the combined thermogravimetry-differential thermal methods. In this study, taking the chalcanthite as the research object, the thermogravimetric-differential thermal analyses were systematically conducted by using synchronous thermal analyzer technology. The results can demonsrate that: (1) DTA curves of low- and medium-weight chalcanthite show 5 dehydration endothermic peaks, while TG curves don’t display obvious weight-loss steps; DTA and TG curves of high-weight chalcanthite samples, on the other hand, illustrate three endothermic peaks, indicating three-step loss of crystalline water; (2) higher weight of samples may cause longer time of internal heat transfer and larger temperature gradient, consequently resulting in the expansion of DTA peak shape and the decline of resolution, as well as the increase of the peak temperature; (3) the weight-loss deviation between the measured and theoretical data are relatively higher in the low-weight samples compared with those in the medium- and high-weight samples; (4) the heating rate can increase the DTA curve peak and thermal inertia as well as the temperature at the thermodynamic equilibrium, causing the temperature lagging behind and the overall peak moving toward high temperature; (5) sample grinding may destroy the structure of the crystal, thereby breaking the relatively weak chemical bond, and thus affect the structure of thermogravimetric-differential thermal analyses. These suggest that the sample weight, heating rate and sample grinding probably have significant effects on the thermogravimetric-differential thermal analyses. Therefore, proper experimental conditions are needed to obtain the accurate results during the thermogravimetric-differential thermal analyses. This study can provide a basis and reference for future synchronous thermal analyses.